Self-help groups for mobilizing tribal youth for entrepreneurship-the experience of Meghalaya N.Prakash - N. Prakash,; P.P. Pal,; M. Sarma, (Journal of Agricultural Extension Management, 2025)
The involvement of Self Help Groups (SHGs) in community development activities has been appraised by the tribal people of Meghalaya. During the initial years of establishment the SHGs used to work in collaboration with Durbar Shnong i.e. the Village Council, for management of common property resources like water, pasture land, forest, village durbar land and others. But gradually the SHGs started concentrating efforts on the development of tribal youth to inculcate an attitude towards employment generation activities. This shift in dimension was supported by Bosco Reach Out, a Guwahati based voluntary organization that took active initiation in setting up at least one self-help group in the villages. The coordination and linkage maintained by this voluntary organization helped the selected SHG members undergo skill-based training programmes in different organizations like ICAR, RRTC etc. as per the aspirations of the members. This has helped the members of such SHGs to come up with a number of enterprises as their subsidiary source of income as well as employment generation